2011
DOI: 10.1007/s11664-011-1716-8
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Post-Etch Copper Residue on Direct Bonded Copper (DBC) Substrates

Abstract: For many years, direct bonded copper (DBC) substrates have proved to be an excellent solution for electrical isolation and thermal management of highpower semiconductor modules. However, in this study we detected a copper residue on the surface of DBC alumina, presumably a result of pattern etching even in industry. As is known, growth of metal dendrites could be observed with the assistance of electric field, temperature, and humidity. Metal dendrites normally grow from the cathode to anode. Silver and copper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…18) However, in spite of these excellent performances, some of the previous studies have reported that DBC showed an unreliable performance due to the oxidation and diffusion of copper through the grain boundary in a high temperature environment (<250 °C). [19][20][21][22][23][24][25] In our previous study, a Ni barrier layer showed poor inhibition of Cu diffusion in hightemperature die-attach applications, but a Ti barrier layer deposited on the DBC surface helped to prevent Cu diffusion into the Ag and consequent Cu oxidation. 25) The traditional 5000 nm Ni-metallized DBC substrates are no longer stable at high temperatures of 250 °C.…”
Section: Introductionmentioning
confidence: 92%
“…18) However, in spite of these excellent performances, some of the previous studies have reported that DBC showed an unreliable performance due to the oxidation and diffusion of copper through the grain boundary in a high temperature environment (<250 °C). [19][20][21][22][23][24][25] In our previous study, a Ni barrier layer showed poor inhibition of Cu diffusion in hightemperature die-attach applications, but a Ti barrier layer deposited on the DBC surface helped to prevent Cu diffusion into the Ag and consequent Cu oxidation. 25) The traditional 5000 nm Ni-metallized DBC substrates are no longer stable at high temperatures of 250 °C.…”
Section: Introductionmentioning
confidence: 92%
“…Sulfur/chromic acid can release large volumes of hazardous substances. Waste ferric chloride solution [3][4][5] is difficult to treat and hard to reuse. Cupric chloride [6,7] includes two types of acidic and alkaline and is the most widely used at present because of its easy regeneration capability and low waste production.…”
Section: Introductionmentioning
confidence: 99%